Maghreb Countries (algeria - Tunisia - Morocco) Towards Islamic Banking - A Comparative Analytical Study – - Chaabnia , Souad (khazzartech الاقتصاد الصناعي, 2023)
This study aims at highlighting the various reforms that the Maghreb countries (Algeria-Tunisia-Morocco) have pursued since their independence in order to financially liberalize their banking sectors and direct them towards Islamic banking. The study has relied on the analytical descriptive approach and the comparative approach. The study concluded that the Maghreb countries have worked to keep pace with the global economic and financial changes by adopting expanded legislative and regulatory policies to ensure the liberalization of their economies, especially their banks. In terms of adopting the Islamic banking, these countries have taken important steps in adopting this type of transactions. However, this is not sufficient and does not fulfil the customers’ aspirations of these countries who wish to obtain a rich and varied assortment of products that meet their financing needs within the framework of Sharia.